Clozapine Regulates Microglia and Is Effective in Chronic Experimental Autoimmune Encephalomyelitis - Ceylan, Ulaş; Haupeltshofer, Steffen; Kämper, Laura; Dann, Justus; Ambrosius, Björn; Gold, Ralf; Faissner, Simon (Frontiers in Immunology, 2021)
Objective Progressive multiple sclerosis is characterized by chronic inflammation with microglial activation, oxidative stress, accumulation of iron and continuous neurodegeneration with inadequate effectiveness of medications used so far. We now investigated effects of iron on microglia and used the previously identified neuroprotective antipsychotic clozapine in vitro and in chronic experimental autoimmune encephalomyelitis (EAE). Methods Microglia were treated with iron and clozapine followed by analysis of cell death and response to oxidative stress, cytokine release and neuronal phagocytosis. Clozapine was investigated in chronic EAE regarding optimal dosing and therapeutic effectiveness in different treatment paradigms. Animals were scored clinically by blinded raters. Spinal cords were analyzed histologically for inflammation, demyelination, microglial activation and iron accumulation and for transcription changes of regulators of iron metabolism and inflammation. Effects on immune cells were analyzed using flow cytometry. Results Iron impaired microglial function in vitro regarding phagocytosis and markers of inflammation; this was regulated by clozapine, reflected in reduced release of IL-6 and normalization of neuronal phagocytosis. In chronic EAE, clozapine dose-dependently attenuated clinical signs and still had an effect if applied in a therapeutic setting. Early mild sedative effects habituated over time. Histologically, demyelination was reduced by clozapine and positive effects on inflammation strongly correlated with reduced iron deposition. This was accompanied by reduced expression of DMT-1, an iron transport protein. Conclusions Clozapine regulates microglial function and attenuates chronic EAE, even in a therapeutic treatment paradigm. This well-defined generic medication might therefore be considered as promising add-on therapeutic for further development in progressive MS.